Carbon dioxide utilization: CO2-based polyurethane foam - Liselotte Karulf; Baljeet Singh; Rustam Singh; Timo Repo (Journal of CO2 Utilization)
CO2, a promising C1 resource, can be permanently fixed in polymers, making it abundant and non-toxic. The development of CO2-based polymers, such as rubbers and plastics, for mainstream industrial applications, could significantly reduce CO2 concentration in the atmosphere and decrease the reliance on fossil resources. Notably, polyether carbonate polyols (PECP) and polycarbonate polyols (PCP) are key CO2-based polyols that can be produced by the reaction of CO2 with epoxides in the presence of a catalyst. These polyols are instrumental in creating carbon-neutral polyurethane foam (PUF). This innovative synthesis method offers numerous advantages over the conventional polycondensation of diisocyanate and polyols method. The use of CO2-based polyols for PUF production is a prime example of CO2 utilization with substantial industrial potential. This review delves into recent advancements in preparing PUF using both isocyanate and non-isocyanate methods with CO2-based polyols, and cyclic carbonates, respectively. PUF, a vital member of the polymer family, boasts a wide range of applications, presenting a significant opportunity to integrate CO2 into existing processes and products, thereby contributing to environmental sustainability.